A Comparison of the European Union and the Southeast Asian Models of Regional Integration - Klecha-Tylec, Karolina (Porównanie modeli integracji Unii Europejskiej oraz Azji Południowo-Wschodniej, 2010)
The European Community is the oldest dialogue partner of ASEAN (both bodies have entered into relations since 1972). The degree of regional integration through trade in Southeast Asia has been rising fast, especially over the two decades. By now economic integration in the European Union and in ASEAN has made enormous progress. Contemporaneously the institutional interaction between the EU and ASEAN (also in the Asia-Europe Meeting (ASEM) officially established in 1996) became an important element of a world economy and global politics. Implementing new regional arrangements and frameworks in East Asia (first of all ASEAN+3 and ASEAN-China FTA) make ASEAN more and more important partner in the region. The Association can even play a part of East Asian hub, taking the advantage of Sino-Japanese rivalry in the region.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 25-34
Keywords: model of integration; ASEAN; the European Union